Influence of IAA-Producing Bacteria and Phosphate Solubilizers from The Rhizosphere of Serbania grandiflora (L.) Pers on The in vitro Germination of Vigna radiata (L.) - Arianti, Septia; Zulkifli, Lalu; Mertha, I Gde; Rasmi, Dewa Ayu Citra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to determine the effect of IAA-producing bacteria and phosphate solvents from the rhizosphere of Serbania grandiflora (L.) Pers on the germination of Vigna radiata (L.). This research began by isolating the rhizosphere bacterium Serbania grandiflora (L.) Pers, which was then characterized by cell morphology, grammatical and morphological characteristics. The ability of bacteria to dissolve phosphate was evaluated qualitatively by observing the presence of clear zones in Pikovskaya media, and quantitatively with a spectrophotometer. The isolate's ability to produce IAA was tested quantitatively using Salkowski reagent, and quantitatively using a spectrophotometer. For the effect of isolates on the growth of green beans, a completely randomized design (CRD) research design was used, with 4 treatments, namely P0 (sterile distilled water); P1 (IAA-producing bacterial culture); P2 (phosphate solubilizing bacterial culture); P3 (IAA producer and phosphate solubilizer). Vigna radiata L. seedling growth test was carried out in vitro on Murphy's medium. The research data were analyzed using the one-way ANOVA test. The results showed that 5 isolates had the ability to dissolve phosphate, with a phosphate solubility index ranging from 1.70-2.14, where isolate RT7 showed the highest value. The isolate's ability to produce IAA at concentrations ranged from 7.1 - 62.7 ppm, with the highest value shown by isolate RT6. The results showed that treatment with IAA-producing bacterial isolates plus phosphate solubilization properties showed a significantly different effect on Vigna radiata L. plant height compared to other treatments.